2022
DOI: 10.3390/fermentation8100556
|View full text |Cite
|
Sign up to set email alerts
|

From Agri-Food Wastes to Polyhydroxyalkanoates through a Sustainable Process

Abstract: The biologically-derived polymers polyhydroxyalkanoates (PHAs) are biodegradable and can be considered a valuable alternative to conventional fossil-based plastics. However, upstream and downstream processes for PHA production are characterized by high energy and chemical consumption and are not economically competitive with petroleum-based polymers. Aiming to improve both the environmental and economical sustainability of PHAs production, in this work, corn straw was used as raw material to obtain a mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The rich composition of the soapstock makes it possible to fully realize the biosynthetic potential of the studied bacterial strains. Similar to our results, previous studies showed effective production of PHAs on media containing different agro-industrial wastes [14,[21][22][23]. It is known that substrates entail major costs in PHA production [2,19].…”
Section: Selection Of Low-cost Substrate For Pha Synthesis By Endophy...supporting
confidence: 92%
“…The rich composition of the soapstock makes it possible to fully realize the biosynthetic potential of the studied bacterial strains. Similar to our results, previous studies showed effective production of PHAs on media containing different agro-industrial wastes [14,[21][22][23]. It is known that substrates entail major costs in PHA production [2,19].…”
Section: Selection Of Low-cost Substrate For Pha Synthesis By Endophy...supporting
confidence: 92%
“…Campanari et al [101] (Table 6, Entry 1) utilized a multi-stage process in which they selected PHA-storing microorganisms under feast and famine (FF) conditions in a sequencing batch reactor (SBR) and found out that the PHA production is widely influenced by the selection of PHA producers, which is in turn influenced by the organic loading rate (ORL). Verdini et al (Table 6, Entry 2) [102] used corn straw saccharified with the aid of microwave technology and obtained a greater yield during scaling up in a stirred tank 3L bioreactor, compared to a shake flask. Moreover, the authors were also able to determine the specific PHA that was being produced, which was poly(3-hydroxybutyrateco-3-hydroxyvalerate) (PHBV).…”
Section: Polylactic Acid (Pla): a Non-toxic Alternative For Mulching ...mentioning
confidence: 99%
“…The agri-food waste and by-products can be used by microorganisms as feedstock for fermentation in the production of biopolymers [81]. Polyhydroxyalkanoates (PHA) and polylactides (polylactic acid) (PLA), in particular, are the most studied polymers to date and are widely used due to their numerous applications [82]. Figure 2 presents a general PHA/PLA production flowchart that follows the sustainable concepts of a closed loop and clean production.…”
Section: Microbial Biopolymer Packagingmentioning
confidence: 99%